Analisis Kepuasan Petani Karet terhadap Kinerja Pasar Lelang di Provinsi Riau Pendekatan Customer Satisfaction Index (CSI) dan Importance Performance Analysis (IPA) - Aung Ezra Al'fatah; Herlyna Novasari Siahaan; Juli Adevia (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Riau Province is one of Indonesia’s major centers of natural rubber production, with Kuantan Singingi Regency serving as its primary contributor. Since 2018, the regency has implemented an auction system for processed rubber (bokar) through the APKARKUSI institution to improve selling prices and reduce farmers’ dependence on intermediaries. However, the absence of a comprehensive evaluation regarding farmers’ satisfaction with APKARKUSI’s performance, coupled with the emerging trend of farmers reverting to conventional marketing systems, presents a critical issue that warrants further investigation. This study aims to analyze the characteristics of rubber farmers participating in the Bokar auction marketing system facilitated by APKARKUSI and to evaluate their satisfaction levels with the institution’s performance. The research was conducted in Kuantan Singingi Regency, which has the largest rubber plantation area in Riau Province and is the only regency to have consistently implemented the bokar auction system since 2018. Data were collected from 96 farmers selected through purposive sampling between December 2024 and January 2025. Analytical methods included descriptive statistics, the Customer Satisfaction Index (CSI), and Importance-Performance Analysis (IPA). The findings reveal that most farmers have more than ten years of farming experience and possess at least a senior high school education, fostering openness to innovation and active participation in the auction system. The CSI score of 90.32%, classified as “very satisfied,” indicates that APKARKUSI’s performance aligns well with farmers’ expectations. IPA results indicate that marketing, information dissemination, and technological aspects fall within Quadrant II (maintain performance), while financing and agricultural machinery procurement fall within Quadrant I (top priority for improvement). These results provide valuable insights into strengthening institutional performance and can serve as a strategic framework for developing more sustainable marketing systems for other agricultural commodities.